PENGARUH KOMUNIKASI, DISIPLIN KERJA DAN KESELAMATAN KERJA TERHADAP KINERJA KARYAWAN PT. ASIA TECH MANUFACTURING INDONESIA - mira yona; Rostaria g (EQUILIBIRIA, 2018)
to Employee Performance PT. Asia Tech Manufacturing Indonesia. As well as to know which variables dominantly affect Employee Performance. The research method used is quantitative analysis with Validdy test, Reliability test, Classical  Assumption  test,  T  test  and  F  test  and  Coeffisient  of  Determination Analysis.The population of this study amounted to 150 employees and sampled 109 respondents as a sample based on the method of Probability Sampling : Simple Random Sampling. The result of the study show the communication, personality and organizational commitment simultaneously or together have a positive andsignificant impact on employee performance PT. Asia Tech Manufacturing Indonesia.   Keywords: Communication, Discipline work, work safety and Employees Performance